2015
DOI: 10.1021/acs.joc.5b00177
|View full text |Cite
|
Sign up to set email alerts
|

Ru-Catalyzed Asymmetric Transfer Hydrogenation of α-Trifluoromethylimines

Abstract: Enantioselective transformation of strong electron-withdrawing acyclic α-trifluoromethylimines to α-trifluoromethylamines through a ruthenium-catalyzed asymmetric transfer hydrogenation has been developed. The method described here is a facile catalytic process with sodium formate as a hydrogen resource and water-dimethylformamide as a cosolvent. The benefit of this enantioselective transformation affords a series of chiral α-trifluoromethylamines with high yields and excellent enantioselectivities (93-99% ee)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…However, further single crystal X-ray crystallographic study confirmed that instead of the chloride counterion, the anion that was really forming the salt was hexafluorophosphate . This fact was also corroborated by 31 P NMR experiment where a septet (J = 714.4 Hz) was identified at δ = -69.15, while in the 19 F NMR experiment, the magnetic equivalence of the six fluorines in the [PF 6 ]anion gave a doublet with a J = 714. 4 Hz at δ = -71.41 (see Figures SI26 and SI27, Supporting Information).…”
Section: Figure 1 Representative Natural Systems Prepared Through Thesupporting
confidence: 53%
“…However, further single crystal X-ray crystallographic study confirmed that instead of the chloride counterion, the anion that was really forming the salt was hexafluorophosphate . This fact was also corroborated by 31 P NMR experiment where a septet (J = 714.4 Hz) was identified at δ = -69.15, while in the 19 F NMR experiment, the magnetic equivalence of the six fluorines in the [PF 6 ]anion gave a doublet with a J = 714. 4 Hz at δ = -71.41 (see Figures SI26 and SI27, Supporting Information).…”
Section: Figure 1 Representative Natural Systems Prepared Through Thesupporting
confidence: 53%
“…[88] Ru(II)-catalysed ATH of α-trifluoromethylimines was also achieved using TsDPEN-based catalysts under aqueous conditions ( Figure 20). [89] Several reports have recently appeared describing the ATH reduction of cyclic sulfamidates and sulfamides, following the report of this in 2010. [90] The synthetic routes to key substrates and their reductions by Rh(III) catalysts are shown in Figure 21.…”
mentioning
confidence: 99%
“…IR (film, NaCl): 3369, 2955, 1712, 1514, 1449, 1435, 1292, 1241, 1201, 1175, 1124, 1082: m/z calcd for C 17 H 17 F 3 6, 153.6, 139.2, 137.8, 135.2, 132.6, 129.4, 129.3, 127.9, 125.0 (q, J(C−F) = 282 Hz), 115.9, 115.0, 61.6 (q, J(C−F) = 30 Hz), 55.8, 26.8. 19 F NMR (CDCl 3 ): −74.1 (d,J = 7.2 Hz). IR (film, NaCl): 3362, 2933, 1720, 1683, 1514, 1464, 1359, 1236, 1169, 1124, 1036 3383, 2837, 1615, 1594, 1511, 1489, 1450, 1232, 1179, 1148, 1118, 1034: m/z calcd for C 15 H 14 F 4 (S)-4-Methoxy-N-(2,2,2-trifluoro-1-(3-methoxyphenyl)ethyl)-aniline (2y).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%